Developement of ceramic cutting insert of alumina (Al2O3) and zirconia / zirconium oxide (ZrO2) for turning tool steel - Shamsudin, Zuraidy (2007)
The production of cutting tool insert using a powder technology is a process that is widely use today especially for ceramic cutting tool. The powder technology that has been use involve three phases which is, firstly the raw material will be grind to nanometer size powder. In second phase, the powder will be compacted using special mold with high pressure, and after that sintering process will take place for the third phase. In this study, two nanometer size ceramic powders will be mixed together with a suitable composition to produce a better final product. This production concept is similarly with the production of ‘ceramic matrix composite’ material which is the reinforce material will be added to the ceramic base material or ceramic matrix. There are several sintering process that can be use for this study, for example, normal sintering process, and hot isocratic process with high pressure furnace.